Habilidades sociais das elites na administração pública: Um estudo na justiça federal em mossoró/rn - Gomes, Anara Luana Nunes (Universidade Federal Rural do Semi-Árido, 2019)
The history of the Brazilian public administration also shelters the history of elites, groups of individuals who hold power, wealth and high social status. From the Empire to the Republic after the 1988 Constitution, the elites are present in the Brazilian public administration, passing through patrimonialism, bureaucracy to new public management. In this work, the presence of elites in the public administration, specifically in the local federal judicial sphere, allowed the hypothesis that it is possible to identify and understand how and what resources these "power groups" use for their reproduction. The objective established in this paper was to discuss and identify the social skills of the federal judicial elite in Mossoró city. For this, we sought to relate theoretically elites, fields, habitus and social skills; describe the trajectory of the Brazilian public administration regarding the models of management and its relationship with the elite concept; and identify and characterize the public elite of the Federal Justice in Mossoró/RN. As for the method, a social research of the descriptive type was carried out, with a qualitative approach, using the technique of bibliographical research to survey the theoretical reference, and later semi-structured interviews to collect the data from the three titular Judges who work in the Federal Court in Mossoró, identified in this study as elite. The analysis of the data collected was made in the light of the concepts of social skills proposed by Neil Fligstein, as well as of fields, habitus and symbolic power of the work of Pierre Bourdieu, thus avoiding generalizations. The judges' social skills were identified in the interviews: being cordial, assuming the role of manager, developing a democratic management based on goals and rewards, praising and enhancing the Federal Justice organization and its servers, being accessible, creating identities or new cultural frameworks and institutionalize these created standards. These actions were classified as social skills for inducing cooperation in the field and favoring the reproduction of this elite, and this confirms the hypothesis raised in the study
Keywords: Administração pública; Elites; Gestão; Habilidades sociais; Public administration; Elites; Management; Social skills; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA